2017
DOI: 10.7554/elife.26138.013
|View full text |Cite
|
Sign up to set email alerts
|

Author response: G protein βγ subunits inhibit TRPM3 ion channels in sensory neurons

Abstract: Transient receptor potential (TRP) ion channels in peripheral sensory neurons are functionally regulated by hydrolysis of the phosphoinositide PI(4,5)P 2 and changes in the level of protein kinase mediated phosphorylation following activation of various G protein coupled receptors. We now show that the activity of TRPM3 expressed in mouse dorsal root ganglion (DRG) neurons is inhibited by agonists of the G i -coupled m opioid, GABA-B and NPY receptors. These agonist effects are mediated by direct inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…First, TRPM3 was shown to be abundantly expressed and functionally active in different brain regions (Oberwinkler and Philipp, 2014). Furthermore, TRPM3 can be modulated by several endogenous brain ligands and receptors (Held et al, 2015b;Badheka et al, 2017;Csanády, 2017;Dembla et al, 2017;Quallo et al, 2017). In addition, TRPM3 was also shown to be targeted by a commonly used anti-convulsion drug, primidone (Krügel et al, 2017), a compound of which the exact molecular actions are up until today still illusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, TRPM3 was shown to be abundantly expressed and functionally active in different brain regions (Oberwinkler and Philipp, 2014). Furthermore, TRPM3 can be modulated by several endogenous brain ligands and receptors (Held et al, 2015b;Badheka et al, 2017;Csanády, 2017;Dembla et al, 2017;Quallo et al, 2017). In addition, TRPM3 was also shown to be targeted by a commonly used anti-convulsion drug, primidone (Krügel et al, 2017), a compound of which the exact molecular actions are up until today still illusive.…”
Section: Discussionmentioning
confidence: 99%
“…In good accordance, signaling pathways decreasing endogenous PtdIns(4,5)P 2 , like phospholipase C activation evoked by M1 or M3 muscarinic acetylcholine receptors, inhibited both recombinant and native TRPM3 Tóth et al, 2015). G βγ subunits of trimeric G-proteins were also shown to be negatively coupled to TRPM3 activity, which underlies inhibition of TRPM3 upon stimulation of several Gprotein-coupled receptors, including G q -coupled M1 muscarinic acetylcholine, B2 bradykinin receptors and G i -coupled M2 muscarinic acetylcholine, D2 dopamine, GABA B , neuropeptide Y, µ-opioid receptors and G s -coupled EP-2 prostaglandin, and A2B adenosine receptors or receptors of somatostatin (Badheka et al, 2017;Dembla et al, 2017;Quallo et al, 2017;Alkhatib et al, 2019). A 10-amino-acid-long domain in TRPM3 was identified that interacted with G βγ proteins.…”
Section: Intrinsic Regulation By Signaling Moleculesmentioning
confidence: 99%
See 1 more Smart Citation